The Province of Malaga’s Inclination for a University. Study of the origin and founding of the Universidad de Malaga on the occasion of its 50th anniversary - Rojo Gallego-Burín, Marina (CIAN-Revista de Historia de las Universidades, 2023)
This paper contributes to the study of the History of Spanish Universities, more particularly that of the University of Malaga. This institution is commemorating ts 50th anniversary, but it is relevant to show that the university vocation of its province is ancient, which makes it a territory of university tradition. In this article we will examine two files, one in the Archive of the Diputación de Málaga and the other in the University Archive of Granada. The first one corresponds to the frustrated attempt to establish the University in 1934, during the Second Republic, in which all politicians, entities and institutions did not agree on its necessity. On the other hand, the file of the University of Malaga corresponds to the whole argumentative apparatus that was used to turn into reality the pretension of creating a University in Malaga .
Keywords: University; Malaga; anniversary; Republic